Wage Formation in Open Economies and the Role of Monetary and Wage-Setting Institutions - Markus Knell (Oesterreichische Nationalbank (OeNB), 2002)
The paper studies the determinants of unemployment in a two-country model, where real wages are the outcome of the strategic interaction between various institutional players (firms, unions, central banks). We show that: (i) the results derived in the recent literature on this topic are not generally robust against the introduction of openness; (ii) the shape of the Calmfors- Driffill curve not only depends on a country's own centralization of wage-bargaining (CWB) but rather on home and foreign characteristics; (iii) the model challenges the established belief that a shift to a monetary union (MU) will (negatively) affect unemployment in all member countries by fundamentally changing the nature of strategic interactions. Under certain assumptions our open-economy model suggests that the formation of a MU has no effect whatsoever on structural unemployment.
Keywords: E50; E58; F41; F42; J51; 330; Wage-Setting; Unemployment; Monetary Union